Editorial: Learning Transformation through Innovation and Sustainability in Educational Practices - Bulent Tarman; Smitha Dev (Research in Social Sciences and Technology, 2018)
In the academic world "Real learning" in any form is an active interaction of human mind with past experience, and that relates to man, machine, materials and ideas. Therefore any teaching and learning process should be aimed at providing ample scope for the learners mind to interact and acquire fruitful experience. Only through this active interaction, the learners and educators can reconstruct his/her experience in light of new experience leading to "Real learning". This enables to enhance the competency, tenacity and inquisitiveness among the scholars. A dedicated and focused approach towards different teaching and learning experience of educators from different parts of the world, especially from the Middle East has been widely discussed in this Special Issue of general Education Conference.